Academic Vocabulary Instruction and Socio-Scientific Issue Discussion in Urban Sixth-Grade Science Classrooms - Relyea, Jackie Eunjung (Archīum Ateneo, 2022)
Given the growing evidence of academic language demands embodied in science practices, this study aimed to design and evaluate the effectiveness of a literacy-science integrated program that emphasized the incorporation of academic vocabulary instruction and collaborative discussion of a socio-scientific issue in sixth-grade science classrooms in an urban school. The treatment students (n = 73) who participated in the intervention had significantly higher academic vocabulary knowledge and scientific argumentation posttest scores than the control students (n = 62). The effect on academic vocabulary knowledge was particularly greater for bilingual students than their monolingual peers. Mediation analyses revealed that the intervention effects on science content knowledge and scientific argumentation were mediated by academic vocabulary knowledge. Findings indicate that science teachers’ instructional scaffolding for academic vocabulary and authentic discourse can not only improve students’ academic vocabulary knowledge but also indirectly affect science content knowledge and scientific argumentation via academic vocabulary knowledge.